Dampak Lokawisata Baturraden terhadap Kondisi Sosial dan Budaya Masyarakat Desa Karangmangu, Kecamatan Baturraden Kabupaten Banyumas - Arina Nindyar Saraswati; Hardiman Hardiman; Zamzam Masrurun; Eki Melina Widanti; Azmy Hanif (Yayasan Literasi Sains Indonesia, 2026)
The Baturraden tourist attraction is nature tourism located in Karangmangu Village, Baturraden District, Banyumas Regency. The Baturraden tourist attraction is leading nature tourism because it has won various awards in the last ten year. This is supported by exciting objects to be visited such as natural scenery from the Mount Slamet hillside, waterfalls, Pancuran Telu, Pancuran Pitu, suspension bridges, Baturraden natural theater, and swimming pools. Based on statistical data, the Baturraden tourist attraction is ranked first with the most visitors.This research was conducted to determine the impact of the Baturraden tourist attraction on the social and cultural conditions of the people of Karangmangu Village as a tourism support village. The impacts were examined by observation, interviews, and literature study.The results of the study show that the Baturraden tourist attraction impacts the social condition that occur in society are increased quality of life, building of new communities, and the emergence of crime. Other impacts are in the form of cultural impacts such as tourist visits affecting the existence of local culture, the commercialization of cultural arts, and open behavior of the community towards tourists. Due to the positive and negative impacts that occurred in the Karangmangu Village community, social and cultural impact management strategy was formulated. The steps taken in community-based tourism impact management are determining the participation role of local communities involved, mapping the impact of tourism, making decisions on managing social and cultural impacts, making efforts to educate the community, monitoring and evaluation.